In Depths - Hiraoka Cloke, George; Luy Tan, Anna (UnderCurrents: Journal of Critical Environmental Studies, 2025)
Stretching hydrophone recordings of diverse marine life with the whirring noises of radars and excavation equipment, In Depths is an acoustic exploration of deep sea entanglement, through which subterranean soundscapes echo and resound from the abyssopelagic to the ocean surface. Drawing upon Stacy Alaimo’s notion of abyssal temporalities, In Depths uses time-stretching production techniques to contemplate subaquatic assemblages, consider the cumulative costs of deep sea mining, and value temporalities of slowness in resistance to the accelerating rhythms of resource extraction. ===== The audio file can be accessed at https://on.soundcloud.com/DdX3rHSoBTp9ccv86